IMPACT OF APPLICATION OF SUPERVISORY PROCEDURES AND FUNCTIONS ON VESSEL SAFETY AT NUNUKAN PORT - Rahman, Faisal; Gunawan, April; Simanjuntak, Marihot (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
The purpose of this study is to investigate the impact of implementing procedures and monitoring functions on vessel safety at Nunukan Port. This study uses a quantitative approach using the smart partial least squares (PLS) method. This method analyzes quantitative data and models the relationships between the variables involved in the study. The study results were obtained by analysis using the Smart PLS method. First, there is a positive correlation between the implementation of effective management procedures at Port Nunukan and the level of vessel safety. This means that the better the control procedures are implemented, the higher the level of vessel safety that can be achieved. In addition, the study found that proper training of port personnel has a positive impact on vessel safety. A port officer with sufficient knowledge and skills to carry out their supervisory duties can significantly improve the safety level of vessels in Nunukan Port. Furthermore, the study shows that coordination among the various actors involved in maritime management, such as authorities, port officials and ship owners, also has a positive impact on vessel safety. Proper cooperation of all involved will increase the effectiveness of supervision and reduce the risk of accidents.